REVIEW OF PREDATORY FLIES OF THE FAMILY DOLICHOPODIDAE (DIPTERA) IN IRAN - Grichanov, I. Ya. (Acta Biologica Sibirica, 2016)
The data on Dolichopodidae from Iran since 1913 are reviewed. Liancalus virens (Scopoli, 1763) is recorded for the first time for Iran. A list of Dolichopodidae of the country includes 114 species.